On‐chip temperature compensation for optical transmitter modules. Issue 3 (1st January 2013) - Sangirov, J.; Park, T.‐W.; Ukaegbu, I.A.; Lee, T.‐W.; Park, H.‐H.
Abstract : On‐chip temperature compensation (TC) for optical transmitter (Tx) modules is reported. The TC block is integrated in common silicon (Si)‐substrate with the Tx and demonstrates the ability to maintain a constant VCSEL output light power without an additional monitoring photodiode. Designed and fabricated in a 0.13 µm technology, the Tx with a TC block operates at up to 5 Gbit/s. A BER of less than 10 − 12 is achieved at a received input power of − 3 dBm, with a 1.3 dBm variation of received power for a temperature increase of 20–100°C at 5 Gbit/s data rate. The percentage error of the temperature compensated Tx output light power is ± 3%. The Tx module consumes a power of 20 mW at 1.3 V, including the TC block.